Influência ambiental na morfometria de insetos - Souto, Kleber Cleanto Faria Lemes (2011)
Morphometric methods associated with multivariate statistical analysis are adequate tools to elucitade biological questions related to character variations within and between populations. Besides, these methods allow to verify the effects of the available resources amount for food suply, the climatic fluctuations and the presence of predators and orher natural enemies in some individual characteristics such as size and symmetry. The aim of this dissertation was to investigate the climatic and the density of occurrence effects on the the size and on the fluctuating asymmetry (FA) of individuals from distinct populations. It was considered on the analysis two Euxesta species (Otitidae = Ulidiidae) from the biological reserve of the Estação Ecológica do Panga and form a guava orchad located at Água Limpa Farm, and also, populations of the aphid Brevicoryne brassicae (L.) (Aphididae) and its associated microhymenopteran hyperparasitoid Alloxysta fuscicornis (Hartig) (Figitidae) in the Glória Experimental Farm, all sites belonging to the Universidade Federal de Uberlândia. The results demonstrate that the temperature variations produce body sizes variations, although it not generates marked effects over the individual s symmetry. Euxesta sororcula (Wiedemann) and Euxesta stigmatias (Loew) (Otitidae = Ulidiidae) populations showed distinct population dynamics strucutures even habiting togheter the same environments. E. sororcula for being more susceptibile to show size and FA variations presents a promissor potential use as a biological indicator of environmental stress. The temperature also affected the density and the size of B.brassicae in the studied system and, once altered these characteristic of this primary host, changes on size and on FA of the hiperasitoids were also produced. Adjustments on the individual and population levels contribute to the population dynamics regulation of investigated species.